Nutritional Assessment and Antioxidant Activities of Different Varieties of Vigna radiata - Riaz Ullah; Zain Ullah; Salem S. Al-Deyab; Muhammad Adnan; Akash Tariq (The Scientific World Journal)
Three cultivars of Vigna radiata, namely, NM-92, NM-98, and NM-06, were analyzed for their proximate composition. The samples were also tested by HPLC for amino acid content. The data showed that all the varieties had same moisture level. The maximum ash content (4.29%) was present in NM-92, and crude fat (2.26%) was highest in NM-98 while NM-06 contained maximum amount of crude protein. About eighteen types of amino acids were detected in each of the three varieties. Acidic amino acids, that is, aspartic and glutamic acids, were in considerable amount ranged from 13 to 23% followed by leucine, isoleucine, alanine, valine, lysine, phenyl alanine, serine, and arginine which fell in the range of 3–8% of total protein. The maximum amount (13.00 and 22.80%) of aspartic and glutamic acids was present in NM-98. Similarly arginine (6.83%) and serine (5.45%) were also in highest amount in this variety. Leucine (7.46%) was maximum in NM-92 variety. NM-06 contained almost all the amino acids in lesser quantity except for few like threonine, proline, glycine, and alanine. It was concluded from the present study that varieties were of different nutritional value and HPLC was a sensitive method for amino acids determination. Antioxidant activities of all three varieties were also assayed and showed significant results.